2015
DOI: 10.1249/mss.0000000000000428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat and Heat Acclimatization on Cycling Time Trial Performance and Pacing

Abstract: PurposeThis study aimed to determine the effects of heat acclimatization on performance and pacing during outdoor cycling time trials (TT, 43.4 km) in the heat.MethodsNine cyclists performed three TT in hot ambient conditions (TTH, approximately 37°C) on the first (TTH-1), sixth (TTH-2), and 14th (TTH-3) days of training in the heat. Data were compared with the average of two TT in cool condition (approximately 8°C) performed before and after heat acclimatization (TTC).ResultsTTH-1 (77 ± 6 min) was slower (P =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
196
5
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(223 citation statements)
references
References 36 publications
18
196
5
4
Order By: Relevance
“…Furthermore, decisions are often subject to a variety of influences including emotional state, previous experience, perception and social context. This perspective is consistent with findings from two recent reviews of pacing [20,21] in which the complexities of making pacing decisions were highlighted, particularly in regard to processing a wide array of situational cues and sensoryperceptual information. The present manuscript adopts a contemporary psychological perspective of decision-making in pacing, which is very accommodating of athleteenvironment interactions.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, decisions are often subject to a variety of influences including emotional state, previous experience, perception and social context. This perspective is consistent with findings from two recent reviews of pacing [20,21] in which the complexities of making pacing decisions were highlighted, particularly in regard to processing a wide array of situational cues and sensoryperceptual information. The present manuscript adopts a contemporary psychological perspective of decision-making in pacing, which is very accommodating of athleteenvironment interactions.…”
supporting
confidence: 90%
“…An overly strong focus on only this leaves other exciting and useful areas of exploring human behaviour in sports context relatively unattended. For example, athlete-environment interactions as described in a recent review [20], are a crucial factor in understanding the regulation of exercise intensity. In this review, a framework is proposed based on ecological psychology and the interdependence of perception and action.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the percentage of peak heart rate maintained in all time trials, as well as the RPE responses (Fig. 5), were similar to those of experienced cyclists undertaking self-paced efforts of similar length/duration in field and laboratory settings (26,30,42).…”
Section: Discussionsupporting
confidence: 65%
“…The lower power output noted at the start of the time trial in the HOT condition was somewhat atypical and may stem from subjects consciously adopting a conservative approach, knowing that four separate time trials had to be performed. Indeed, power output in the heat usually matches that of cooler conditions for the first 10 -15 min of time trials (10,27,28,30,42,46), unless participants are inexperienced at performing such tasks (40), or the self-paced effort is preloaded with exercise in the heat (9). Hettinga et al (18) also showed that cycling in the heat decreases gross efficiency by 0.9% relative to cooler conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation